Stabilność cen w strefie euro - definicja i znaczenie dla krajów członkowskich - Błaszczyk, Paweł (1932- ) (Prince Stability in the Euro Area - Definition and Importance for Member Countries, 2008)
The price stability is the widespread goal of monetary policy. But it does not mean that it is definitely good for society and economy. In fact, there are also negative consequences, especially for the monetary union like EMU. Their importance depends on correctness of definition of price stability for the practical purposes. The main aim of this article is a presentation of the definition of EMU definition of price stability and their threats for member countries. First of all four phenomena are pointed out: threats of deflation, downward rigidities of nominal wages, zero bound of nominal interest rates and inflation differentials in the euro area. To realize this aim, procedure of definition of price stability is proposed in the first part of the article. It allows to understand the essence of price stability in the transparent way. In the second part, potential threats of price stability are indicated. In the third and last part, definition and their threats of EMU price stability are presented. The importance of inflation differentials is emphasized. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 80-90